Estudo da preparação e das propriedades estruturais de catalisadores para a transformação do metano em gás de síntese e hidrocarbonetos - Mortola, Vanessa Bongalhardo (2010)
Pt catalysts supported on CeO2-La2O3-Al2O3, with different mixed oxide compositions, and CeO2-ZrO2-Al2O3, prepared using three different routes, were synthesized by sol gel technique. The samples were characterized using thermal analysis, N2 adsorption, X-ray diffraction, diffusive reflectance spectroscopy, Fourier transform infrared spectroscopy of CO adsorption and high resolution transmission electronic microscopy. The Pt dispersion was determined from the data of cyclohexane dehydrogenation rate. In situ temperature programmed reduction and Xray absorption near edge structure using redox treatments were performed trying to find a better understanding for the sample behaviors in the reaction conditions. The catalysts were evaluated in the steam reforming and partial oxidation of methane. In the Pt/CeO2-La2O3-Al2O3 catalysts, the substitution of La for Ce caused a higher stability of CeIII in the alumina structure and higher metal electron density. The oxidation at high temperature caused the Pt agglomeration, on the other hand the reduction treatment lead to a support re-dispersion. The mixed oxides samples with elevated ceria content showed higher activity in the steam reforming and partial oxidation of methane. This behavior was attributed to the ability of promoting the gasification of coke. For the Pt/CeO2-ZrO2-Al2O3 samples, the solid solution between CeO2 and ZrO2 was dependent on the calcination temperature. Phase segregation was observed for the sample calcined at 950ºC, which decreased the catalytic activity. It was attributed to a smaller O* mobility in this sample.